A comparative study on awareness about malaria and dengue among the tribal and urban population of Madhya Pradesh - Dudi, Jitendra Kumar; Dogne, Chandragopal; Afrin, Sana; Singh, Abhay; Raghunath, Deepa; Bansal, S. B.; Yuwane, Praveen; Chellaiyan, D. Vinoth Gnana (International Journal Of Community Medicine And Public Health, 2022)
Background: World health organisation (WHO) stresses the importance of education and public awareness of vector-borne diseases. The present study attempts to assess the knowledge, attitude and behavioral practices regarding clinical signs, symptoms, transmission and preventive measures of malaria and dengue. Methods: One tribal (Barwani) and one non-tribal district (Indore) of Indore division of the state of Madhya Pradesh. These two districts were identified based on the simple random sampling technique using chit method of all the 8 districts covered under Indore division. Study design was cross sectional study. Study population were individuals more than 18 years of age from general population residing in Indore and Barwani districts of MP. Results: The 78.1% study subjects did not know the type of mosquito responsible for transmission of malaria and 92.44% study subjects had no idea about the type of mosquito involved in dengue transmission. The 37.8% study subjects did not know the common breeding site of female Anopheles mosquitoes, 28.9% study subjects knew that stagnant clean water was the breeding site of female Anopheles mosquitoes and 54.7% study subjects had no idea about the breeding place of Aedes mosquito. Only 29.5% study subjects were aware that most frequent time of female anopheles bite was at dusk and dawn. Conclusions: Awareness regarding the type of mosquito, its breeding place and biting time was poor. Knowledge regarding symptoms of malaria was better as compared to that of dengue. Awareness practice regarding source reduction was poor in study population.